Some Chlorophycean Algae From Maipokhari Lake, Ilam, East Nepal - Rai, Shiva Kumar (Journal of Natural History Museum, 2009)
The present communication describes the morpho-taxonomy of ten chlorophycean algae from Maipokhari lake, Ilam. They belong to eight genera viz. Scenedesmus (1), Cylindrocapsa (1), Netrium (2), Closterium (2), Euastrum (1), Cosmarium (1), Staurodesmus (1), and Staurastrum (1) under four families viz. Scenedesmaceae (1), Cylindrocapsaceae (1), Mesotaeniaceae (2), and Desmidiaceae (6). Out of these, two genera and six taxa are new records for Nepal. Key Words: Algae; Chlorophyceae; Cylindrocassa; Staurodesmus; Mai Pokhari lake; Nepal. Journal of Natural History Museum Vol. 24, 2009, Page: 1-8